Prototype Sistem Pengendali Peralatan Elektronik Dan Monitoring Keamanan Gedung Berbasis Short Message Service - Hetty Meileni (MANAJEMEN INFORMATIKA, 2009)
In relation with wireless technology development, one of the GSM (Global System for Mobile Communication) technology, which is more inexpensive and with wider abroad global range capacity, consequence use of the cellular phones not only for specific community but also all the community level. SMS (Short Message Service) is one of the facility cellular phone which was known by every people. Besides it is inexpensive in operational cost, this facility could be also used for communicating and transferring information in real time so that this facility is one of the best choice for every people even though other facilities such as EMS or MMS were also developed. Beside communication is one of human needed purpose, security is also become human needed. One of the examples is the home security system. With the high human activities to fulfill their economics need, it is reducing their time for being at home, gathering with their family and also to protect the security of their houses. This condition create writer to conduct experiment and make instruments to monitor and control the security system from far away with effectively and efficiently. Hand phone with SMS facilities which is used for interchange information by remote and wireless, could be used for the one of the best solution to control remote home security system. By using additional computer and technology, it could be make security computer system with effective and efficient power and space. Hand phone could be use as an alternative facility to control remote home security. To implement the above experiment, writer try to design control system which is control home electric appliances using computer facilities at home. It is preparing hardware and software to control electric appliances at home for switch on and switch off automatically such as electric power, electronic equipment, radio and television including for home security monitoring by using SMS.